Peran Pelatihan, Self Efficacy, dan Recognition dalam Meningkatkan Kinerja Karyawan pada CV. Prima Sealindo Engineering - Sari, Ika Febirillah; Ubaidillah, Hasan; Sumartik, Sumartik (JURNAL ADMINISTRASI & MANAJEMEN, 2024)
The aim of this research is to determine employee performance at CV. Prima Sealindo Engineering Employee Performance. This research uses the independent variables training (X1), self-efficacy (X2), and recognition (X3), while the dependent variable is employee performance (Y). This research method The approach used in this research is quantitative. The population was 108 employees, the sample used a saturated sampling technique. Saturated sampling technique is a sample determination technique if all members of the population are used as research samples. Data collection in this research was by distributing questionnaires to respondents using a manual questionnaire. The software is called SPSS. Data analysis techniques include testing standard assumptions and multiple linear regression analysis. In hypothesis testing, the R2 test, t test and F test are used. The results of this research are to compare the sig values. F with α = 0.05. The significant value of F 0.000 is smaller than the value of α = 0.05. rejected so that the results obtained show that there is a significant simultaneous influence between variables X1 and X2, X3 on variable Y. This means that training, self-efficacy and recognition simultaneously influence employee performance.